Los impactos generados por la pandemia COVID – 19 en el destino turístico Puerto Malabrigo - Aldave Mimbela, Milagros del Pilar (2022)
The present thesis called, The impacts generated by the COVID-19 pandemic in the_x000D_ tourist destination Puerto Malabrigo, was to determine the impacts that the pandemic_x000D_ has generated as in the tourist plant as in the demand that visits Puerto Malabrigo._x000D_ The result of the thesis determined that the most visible impacts that leaves the COVID - 19 pandemic, is the loss of employment of the workers who worked in the service provider companies and the temporary closure of businesses in the locality._x000D_ In addition, tourism companies had to implement biosafety protocols adapting to the new state measures, generating additional investment in them. On the other hand, tourist demand was affected since there was a reduction of 15,411 tourists between 2019 and 2020; in the following year there was a minimal recovery of 2,867 visitors._x000D_ The general conclusion is manifested in the momentary suspension of hotels and_x000D_ restaurants, because it was not known how to act against this new virus and in a certain way to prevent its spread._x000D_ In the present investigation, the synthetic analytical and ethnographic methods were_x000D_ applied, as for the techniques that were used in the field stage; it was the poll, direct_x000D_ observation and interview.